Optimization of acid orange II degradation using Fe3-xMnxO4-MKSF catalyst in heterogeneous fenton-like reaction via response surface methodology / Amirah Annasuha Azmi … [et al.] - Azmi, Amirah Annasuha; Alrozi, Rasyidah; Zubir, Nor Aida; Kamaruddin, Mohamad Anuar (Universiti Teknologi MARA Cawangan Pulau Pinang, 2025)
In this study, the operational conditions for acid orange II (AOII) degradation in a heterogeneous Fenton-like reaction using a clay-supported Fe3-xMnxO4 (Fe3-xMnxO4-MKSF) catalyst were optimized using response surface methodology (RSM). A standard RSM called a central composite design (CCD) experiment was used to determine the effects of four operational variables: pH solution, catalyst dosage, concentration of H2O2 and initial concentration of AOII on the percentage of AOII removal. Based on the analysis of variance (ANOVA), the model exhibited a correlation coefficient (R2) of 0.9672 which demonstrated approximately 96% of target function variation. The optimal operational conditions were obtained at 2.5 pH solution, 0.4 g/L catalyst dosage, 15 mM H2O2 concentration and 35 mg/L AOII initial concentration which resulted in 86.72% of AOII degradation. The experimental results showed good agreement with the values predicted by the model at optimal conditions, exhibiting relative differences of less than 5%. These findings provide valuable insights into the interaction of four key variables affecting AOII degradation during the heterogeneous Fenton-like reaction using Fe3-xMnxO4-MKSF catalyst.